EDUKASI KESEHATAN REPRODUKSI SEBAGAI UPAYA PROMOSI KESEHATAN DI SMPN 5 KOTA PADANG - Masrizal Masrizal; Linda Khamelia; Arbimes Arbimes (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2019)
Lifestyle and information as well as various factors affect the knowledge, attitudes and changes in the lives of adolescents who then influence about their recovery health life. Based on observations, SMPN 05 Kota Padang already has PIK-KRR but is still not good in terms of improving the PIK-KRR program. Through the empowerment of the Reproductive Cadre Team, it is hoped that they can be both mobilizers and promoters in increasing knowledge and attitudes for other students and reducing promiscuity in the School Environment. In general, the output target to be achieved in this service is to create and empower students at SMPN 05 Padang City, providing skills and knowledge about health education from an early age. Because this will be a pilot as a future school for other regions. This activity consisted of outreach activities, the Formation and Empowerment of the Reproductive Health Cadre Team, the Implementation Evaluation and Sustainability Program. Summary Health education activities were carried out smoothly by the team of the Faculty of Public Health of Andalas University on August 31, 2018 at SMPN 5 Padang City, with the aim of this educational to class 9. This activity was attended by 64 male and female students. It is expected that students can be involved in their daily lives will also be even better if they can become cadres and examples for their other peers.